Risk Factors for Bullying in Adolescents at SMA Negeri 1 Limboto - Nur Uyuun I. Biahimo; Firmawati Firmawati; Inne Ariane Gobel; Aldawati A. Husuna (Universitas Ibn Khaldun Bogor, 2024)
Bullying is an act of physical and verbal violence when the bully degrades and threatens the victim so that the victim is unable to resist. Bullying behavior has a negative impact, very disturbing and dangerous for adolescents if it is not immediately addressed. The purpose of this study was to determine the risk factors for bullying in adolescents at SMA Negeri 1 Limboto. This study used an analytical survey design, a population of 645 students of grades X and XI of SMA Negeri 1 Limboto, a sample of 86 students of grades X and XI of SMA Negeri 1 Limboto, the type of static random sampling sample, the instrument used was a questionnaire, the statistical test used in this study was a logistic regression test and using univariate analysis and bivariate analysis. The results obtained were the risk factors that most influenced bullying behavior, namely family factors with an R Square value of 74%, then media factors with an R Square value of 56%, and self-control bullying factors with an R Square value of 32%. The conclusion is that family factors are the most risky factors for bullying with the highest R square value, the suggestion from this study is that the better the family parenting style, the impact on the behavior produced by the child himself.